The effect of fibre type in a diet containing fine maize to improve the performance and health of pigs during the final finisher phase - Jansen van Rensburg, Christine (University of Pretoria, 2025)
Dissertation (MSc Agric (Animal Science))--University of Pretoria, 2024.